Soft and hard carbon composite material precursor, soft and hard carbon composite material and preparation method and application of soft and hard carbon composite material

Through liquid phase intermolecular self-assembly technology, a highly uniform and tightly bonded soft and hard carbon composite material precursor was prepared, which solved the problems of poor mixing uniformity and weak bonding force in the prior art, and significantly improved the circulation stability of the material.

CN119750552APending Publication Date: 2025-04-04NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411897611.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the mixing uniformity of soft and hard carbon composites and the weak phase interface binding force are poor, resulting in poor cycle stability and unsatisfactory reaction kinetics in potassium ion batteries.

Method used

Through liquid phase intermolecular self-assembly, soluble dianhydrides are hydrolyzed in a strong alkali solution, and then mixed with organic substances with rich hydroxyl groups to adjust the pH value, induce targeted self-assembly at the molecular level, and prepare a highly uniform and tightly bound soft and hard carbon composite material precursor with a highly uniform phase interface.

Benefits of technology

The high uniformity and phase interface bonding force of soft and hard carbon composite materials are achieved, which significantly improves the structural stability of the material and the cyclic stability as the negative electrode of the potassium ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750552A_ABST
    Figure CN119750552A_ABST
Patent Text Reader

Abstract

The invention discloses a soft and hard carbon composite material precursor, a soft and hard carbon composite material as well as a preparation method and application of the soft and hard carbon composite material. The preparation method of the soft and hard carbon composite material precursor comprises the following steps: fully hydrolyzing a soluble dianhydride substance in a strong alkali solution to obtain a hydrolysis solution; mixing the hydrolysis solution with soluble organic matters with rich hydroxyl groups, adjusting the pH value of the obtained mixed solution to 4-7, and inducing targeted self-assembly at a molecular level to prepare the soft and hard carbon composite material precursor. The soft and hard carbon composite material precursor is subjected to carbonization treatment to prepare the soft and hard carbon composite material. The soft and hard carbon composite material prepared on the basis of a chemical bonding principle and a liquid phase intermolecular self-assembly technology has a strong synergistic effect; the hard carbon derived from the organic matter which is rich in hydroxyl and easy to dissolve in water is adopted, so that a certain storage capacity is provided, and the structural stability of the material and the cycling stability of the negative electrode of the potassium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite material precursor, and in particular to a method for preparing a soft and hard carbon composite material precursor by liquid phase intermolecular self-assembly, as well as corresponding soft and hard carbon composite materials and preparation methods and applications thereof, belonging to the technical field of chemical synthesis. Background Art

[0002] Graphite has a large volume change during the insertion / extraction of potassium ions, poor cycle stability, and a theoretical potassium storage capacity of only 273 mAh / g, so the application of graphite in potassium ion batteries is limited. Studies have found that amorphous carbon (including soft carbon and hard carbon) with an adjustable structure exhibits extremely attractive potassium storage behavior. However, the traditional composite process is to physically premix the two precursors before carbonization. The disadvantage of this method is that the mixing uniformity between the two is poor, and the interface contact is weak, severe phase separation will occur, and it is not enough to produce a strong synergistic effect. Furthermore, patent CN118367130A first prepares the carbonization product of reed straw, then coats a layer of asphalt on its surface, and then performs secondary carbonization to obtain asphalt-derived soft carbon coated with reed straw-derived hard carbon. Although the effect of this method is better than that of physical mixing, there is also a significant alternating interface between soft and hard carbon. Patent CN 115849332 A further improves the mixing method by selecting a suitable solvent system, dissolving the soft carbon precursor and the hard carbon precursor in the selected solvent system, and then separating the two from the solvent at the same time to achieve the maximum uniform mixing of the two. Then, in the subsequent heat treatment process, the two may be cross-linked and fixed, thereby increasing the binding force between the soft and hard carbons. However, it is unsatisfactory that the solubility and precipitation rate of the soft carbon precursor and the hard carbon precursor in the same solvent are different, which will eventually cause local enrichment of the hard carbon region or the soft carbon region in the product, deteriorating the reaction kinetics and cycle stability of such regions. Summary of the invention

[0003] The main purpose of the present invention is to provide a method for preparing a soft and hard carbon composite material precursor by liquid phase intermolecular self-assembly, so as to overcome the shortcomings of the prior art.

[0004] Another object of the present invention is to provide a soft and hard carbon composite material and a preparation method thereof.

[0005] Another object of the present invention is to provide applications of the soft and hard carbon composite material.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0007] An embodiment of the present invention provides a method for preparing a soft and hard carbon composite material precursor, which comprises:

[0008] The soluble dianhydride substances are fully hydrolyzed in a strong alkaline solution to obtain a hydrolyzed solution.

[0009] The hydrolysis solution is mixed with a soluble organic matter rich in hydroxyl groups, and the pH value of the obtained mixed solution is adjusted to induce targeted self-assembly at the molecular level to obtain a soft and hard carbon composite material precursor.

[0010] In some embodiments, the soluble dianhydride substance has two acetyl groups, and the soluble dianhydride substance includes any one or a combination of two or more of 3,4,9,10-perylenetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, cyclobutanetetracarboxylic dianhydride, bisphenol A type diether dianhydride, pyromellitic dianhydride, and 1,4,5,8-naphthalenetetracarboxylic anhydride.

[0011] In some embodiments, the soluble organic matter having abundant hydroxyl groups includes any one of glucose, fructose, sucrose, and maltose, or a combination of two or more thereof.

[0012] The embodiment of the present invention further provides a soft and hard carbon composite material precursor prepared by the above-mentioned preparation method, wherein the soft and hard carbon composite material precursor is highly uniform and has a close interface.

[0013] An embodiment of the present invention further provides a method for preparing a soft and hard carbon composite material, which comprises: in a protective atmosphere, carbonizing the soft and hard carbon composite material precursor obtained by the above-mentioned preparation method to obtain the soft and hard carbon composite material.

[0014] The embodiment of the present invention also provides a soft and hard carbon composite material prepared by the above preparation method.

[0015] The embodiments of the present invention also provide applications of the aforementioned soft and hard carbon composite materials in the field of battery energy storage.

[0016] Correspondingly, an embodiment of the present invention further provides a potassium ion battery negative electrode material, which includes the aforementioned soft and hard carbon composite material.

[0017] Compared with the prior art, the soft and hard carbon composite materials prepared by the present invention in liquid phase by intermolecular self-assembly have the following characteristics:

[0018] 1) The soft and hard carbon composite materials prepared by the present invention based on the chemical bonding principle and liquid phase molecular self-assembly technology have a strong synergistic effect;

[0019] 2) The present invention uses chemical bonding to connect the two precursors, which enhances the interaction between the soft and hard carbon interfaces and avoids phase separation between the two components;

[0020] 3) The present invention uses hard carbon derived from organic matter that is rich in hydroxyl groups and easily soluble in water, which not only provides a certain storage capacity but also improves the cycle stability of the material as a negative electrode of a potassium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is an infrared spectrum of the soft and hard carbon composite material precursor prepared in Example 1 of the present invention;

[0023] Figure 2 This is a Raman spectrum of the soft and hard carbon composite material prepared in Example 1 of the present invention;

[0024] Figure 3a and Figure 3b This is a SEM image of the soft and hard carbon composite material precursor prepared in Example 1 of the present invention;

[0025] Figure 4 TEM image of the soft and hard carbon composite material prepared in Example 1 of the present invention;

[0026] Figure 5 This is a charge and discharge cycle performance diagram of the soft and hard carbon composite material prepared in Example 1 of the present invention as a negative electrode material for a potassium ion battery at a current density of 1000 mA / g. DETAILED DESCRIPTION

[0027] In view of the defects of the existing soft and hard carbon precursor preparation processes, such as poor mixing uniformity and weak interface bonding force, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. That is, inspired by the combination of hydroxyl and carboxyl groups to form ester groups, a method for preparing soft and hard carbon composite material precursors by liquid phase intermolecular self-assembly is provided, thereby constructing soft and hard carbon composite material precursors with super strong synergistic effects.

[0028] The technical solution, its implementation process and principle are further explained as follows. However, it should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described in the following (embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here.

[0029] As one aspect of the technical solution of the present invention, a method for preparing a soft and hard carbon composite material precursor by intermolecular self-assembly in a liquid phase includes:

[0030] The soluble dianhydride substance is fully hydrolyzed in a strong alkaline solution to obtain a hydrolyzed solution;

[0031] The hydrolysis solution is mixed with a soluble organic matter rich in hydroxyl groups, and the pH value of the obtained mixed solution is adjusted to induce targeted self-assembly at the molecular level to obtain a soft and hard carbon composite material precursor.

[0032] In some specific embodiments, the soluble dianhydride substance has two acetyl groups, and the soluble dianhydride substance can include any one or a combination of two or more dianhydride substances such as 3,4,9,10-perylenetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, cyclobutanetetracarboxylic dianhydride, bisphenol A type diether dianhydride, pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, etc., but is not limited to this.

[0033] In some specific embodiments, the concentration of the soluble dianhydride substance in the strong alkaline solution is 0.005-0.5 mol / L.

[0034] In some specific embodiments, the strong alkaline solution may include any one or a combination of two or more of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, etc., but is not limited thereto.

[0035] Furthermore, the concentration of the strong alkaline solution is 0.01-1 mol / L.

[0036] In some preferred embodiments, the preparation method specifically comprises: adding a soluble dianhydride substance to a strong alkaline solution, stirring until fully hydrolyzed, and obtaining a hydrolyzed solution; the stirring time is 2 to 12 hours. The hydrolysis used in the present invention is to reduce the two acetyl groups in the soluble dianhydride compound to the state before dehydration, such as the O=COC=O group in pyromellitic dianhydride. After hydrolysis, the COC bond breaks and is converted into two O=CO- groups, which is convenient for subsequent polymerization with hydroxyl-rich organic matter to obtain a soft and hard carbon composite material precursor prepared by intermolecular self-assembly.

[0037] In some specific embodiments, the soluble organic matter having rich hydroxyl groups may include any one or a combination of two or more of glucose, fructose, sucrose, maltose, etc., but is not limited thereto.

[0038] In some preferred embodiments, the preparation method specifically includes: adding a soluble organic substance rich in hydroxyl groups to the hydrolysis solution, and after uniform dissolution, titrating the resulting mixed solution with an acid solution to a pH value between 4 and 7, and continuing to stir for 1 to 6 hours. Because the condensation of carboxyl groups (R-COOH) and hydroxyl groups (R-COH) to form ester groups (R-COO-R) needs to be carried out in an acidic environment, and the ester group is also unstable in an alkaline environment and will hydrolyze again, it is necessary to adjust the solution pH value of the reaction system to between 4 and 7.

[0039] In some specific embodiments, the acid solution may include any one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc., but is not limited thereto.

[0040] Furthermore, the concentration of the acid solution is 0.01-2 mol / L.

[0041] In some specific embodiments, the ratio of the dianhydride compound to the hydroxyl-containing compound depends on the number of carboxyl groups after hydrolysis of the soluble dianhydride substance and the number of hydroxyl groups in the basic building blocks of the soluble organic matter rich in hydroxyl groups, and the ratio of carboxyl groups to hydroxyl groups is between 4:1 and 1:6.

[0042] Among them, in some more specific embodiments, the specific steps of preparing the soft and hard carbon composite material precursor by constructing a chemical bonding method of the present invention are as follows:

[0043] (1) Add a soluble dianhydride compound to a certain concentration of strong alkaline solution and stir for 2 to 12 hours to fully hydrolyze it;

[0044] The strong alkali solution comprises one or more of a sodium hydroxide solution, a potassium hydroxide solution, and a calcium hydroxide solution; the concentration of the strong alkali solution is 0.01 to 1 mol / L;

[0045] The dianhydride compound includes but is not limited to one or more of 3,4,9,10-perylenetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, cyclobutanetetracarboxylic dianhydride, bisphenol A type diether dianhydride, pyromellitic dianhydride, and 1,4,5,8-naphthalenetetracarboxylic anhydride;

[0046] (2) Adding a soluble organic substance rich in hydroxyl groups to the solution of the fully hydrolyzed dianhydride compound, after uniform dissolution, titrate the resulting mixture with an acid solution of a certain concentration to a pH value between 4 and 7, and continue stirring for 1 to 6 hours after the titration is completed.

[0047] The soluble organic matter having rich hydroxyl groups includes but is not limited to one or more of glucose, fructose, sucrose, maltose, etc.;

[0048] The acid solution comprises one or more of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid; the concentration of the acid solution is 0.01 to 2 mol / L;

[0049] The ratio of the dianhydride compound to the hydroxyl-containing compound depends on the number of carboxyl groups after hydrolysis of the dianhydride compound and the number of hydroxyl groups in the basic constituent unit of the hydroxyl-containing compound, and the ratio of carboxyl groups to hydroxyl groups is between 4:1 and 1:6;

[0050] (3) The product is separated by centrifugation or filtration, washed with deionized water and ethanol three times, and then fully dried in a blower oven at 60-80° C. for 12 h.

[0051] (4) The product is then ground and crushed, and a soft and hard carbon composite material precursor is obtained which is highly uniform and has a tight interface.

[0052] In summary, the present invention prepares a soft and hard carbon composite material precursor by constructing a chemical bonding method. The preparation method uses a soluble dianhydride substance having two acetyl groups and a soluble organic substance rich in hydroxyl groups as the main raw materials. A certain amount of dianhydride substance is fully dissolved in a strong alkaline solution, and then a certain amount of organic matter rich in hydroxyl groups is dissolved in the above solution. Subsequently, the resulting mixture is titrated with an acid solution (inorganic acid) to induce targeted self-assembly at the molecular level to form a compound to obtain a product. After stirring for a period of time, the product is separated, washed and dried, and then the product obtained by grinding and crushing is a soft and hard carbon composite material precursor with high uniformity and tight interface bonding.

[0053] As another aspect of the technical solution of the present invention, it also relates to a soft and hard carbon composite material precursor, and the soft and hard carbon composite material precursor is prepared by the above-mentioned preparation method.

[0054] Furthermore, the soft and hard carbon composite material precursors prepared by the present invention are highly uniform and have close interface bonding.

[0055] The present invention mainly adopts targeted reaction between functional groups under liquid phase conditions for bonding, so that the interfaces of two precursors are more tightly bound at the molecular level, thereby obtaining a soft and hard carbon composite material precursor with high uniformity and close interface connection.

[0056] As another aspect of the technical solution of the present invention, it also relates to a method for preparing a soft and hard carbon composite material, which comprises:

[0057] The soft and hard carbon composite material precursor prepared by the above preparation method is carbonized in a protective atmosphere to prepare the soft and hard carbon composite material.

[0058] In some specific embodiments, the carbonization treatment comprises: firstly heating at 1-5°C min -1 The temperature is raised to 500-700°C at a rate of 1-5°C / min for 1-5h, then raised to 800-900°C at a rate of 1-5°C / min for 1-5h, and finally raised to 1100-1300°C at a rate of 3-10°C / min for 2-6h to complete the carbonization treatment.

[0059] Furthermore, the protective atmosphere includes an argon atmosphere, but is not limited thereto.

[0060] In some more preferred embodiments, the preparation method of the soft and hard carbon composite materials specifically includes: transferring the soft and hard carbon composite material precursors to a tubular furnace using a graphite boat and carbonizing them under argon protection (carbonization procedure of 2-4°C / min to 550-650°C for 2-4h, 2-5°C / min to 800-850°C for 1-3h, and then 3-8°C / min to 1100-1200°C for 2-5 hours), and naturally cooling to room temperature to obtain the soft and hard carbon composite materials.

[0061] In summary, the method for preparing the soft and hard carbon composite material is to sinter the soft and hard carbon composite material precursor in a tubular furnace under an argon atmosphere, and construct a soft and hard carbon composite material with super synergistic effect as the negative electrode material of the potassium ion battery through a simple chemical bonding method. The material tightly bonds the soft and hard carbon together through chemical bonding, thereby generating a strong synergistic effect, improving the structural stability of the material and the cycle stability as the negative electrode of the potassium ion battery.

[0062] As another aspect of the technical solution of the present invention, it also relates to a soft and hard carbon composite material obtained by the aforementioned preparation method, which has a tightly bonded phase interface and a highly uniform and ordered soft / hard carbon distribution.

[0063] Furthermore, the composite material obtained by the above preparation method greatly enhances the interaction force at the soft and hard carbon interfaces, thereby greatly improving the synergistic effect between the two, and thus exhibits excellent performance in battery energy storage.

[0064] As another aspect of the technical solution of the present invention, it also relates to the application of the soft and hard carbon composite materials in the field of battery energy storage.

[0065] Furthermore, the application includes: application of the soft and hard carbon composite material in the negative electrode of a potassium ion battery.

[0066] As another aspect of the technical solution of the present invention, it also relates to a potassium ion battery negative electrode material, which includes the aforementioned soft and hard carbon composite material.

[0067] Furthermore, the soft and hard carbon composite material is used as a negative electrode material for a potassium ion battery. After 500 cycles at a current density of 1000 mA / g, its discharge reversible specific capacity can be maintained above 100 mAh / g.

[0068] The soft and hard carbon composite materials prepared by the present invention based on the chemical bonding principle and liquid phase molecular self-assembly technology have a strong synergistic effect. The use of hard carbon derived from organic matter with rich hydroxyl groups and easy to dissolve in water not only provides a certain storage capacity but also improves the structural stability of the material and the cycle stability as the negative electrode of the potassium ion battery.

[0069] Through the above technical scheme, the present invention provides a precursor for preparing a soft and hard carbon composite material by a chemical bonding method. The precursor mainly adopts chemical bonding between hard carbon precursor molecules and soft carbon precursor molecules to prepare a precursor that is evenly distributed and firmly bonded between molecular layers. Then, the corresponding soft and hard carbon composite material is prepared by heat treatment. This method greatly enhances the strength of the soft and hard carbon interface bonding, improves the synergy between soft carbon and hard carbon, and inhibits phase separation during the cycle process, thereby showing excellent potassium storage performance.

[0070] The present invention is further described in detail below in conjunction with several preferred embodiments and the accompanying drawings. The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any combination of the specific embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention. The experimental methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or under the conditions recommended by the manufacturer.

[0071] Example 1

[0072] Add 784 mg of 3,4,9,10-perylenetetracarboxylic dianhydride to 100 mL of 0.1 mol / L sodium hydroxide solution; seal with plastic wrap and stir for 6 h to fully hydrolyze. Then, add 360 mg of glucose to the above solution and stir magnetically for 1 h to disperse and dissolve (n 羧基 :n 羟基 =2:5). Subsequently, the obtained mixed solution was titrated to neutrality with 1 mol / L HCl solution and magnetically stirred for 2 hours. The obtained product was filtered and washed with deionized water and ethanol three times. Then it was dried in a 60°C forced air oven for 12 hours to obtain an orange-red soft and hard carbon composite material precursor prepared by liquid phase intermolecular self-assembly. The synthesized precursor was characterized and tested by infrared spectrometer, such as Figure 1 As shown, at 1694 and 1188 cm -1The absorption peaks at are generated by the vibration of -C=O bond and -CO bond, which fully proves the chemical bonding between the precursors prepared by liquid phase molecular self-assembly. The dried precursor is loaded into a graphite boat and transferred to a tube furnace. Under argon protection, the temperature is raised to 600℃ at 3℃ / min and maintained for 2h, then raised to 800℃ at 4℃ / min and maintained for 2h, and then raised to 1200℃ at 5℃ / min and maintained for 3 hours for carbonization. After naturally cooling to room temperature, a black powder product is obtained. Figure 2 As shown, the obtained composite carbon material was characterized by Raman spectrometer. D / I G The value is 0.93, indicating that the material contains abundant defects. The cold field scanning electron microscope image shows that the morphology of the prepared product is nanosheet-like (such as Figure 3a and Figure 3b ), transmission electron microscopy showed the alternating appearance and tight dissociation of soft / hard carbon regions (as shown in Figure 4 As shown in Figure 2, the hard carbon is evenly dispersed in the soft carbon. The obtained product is used as the negative electrode material of potassium ion battery. After 500 cycles at a current density of 1000mA / g, its reversible specific capacity can be maintained above 101.4mAh / g (as shown in Figure 2). Figure 5 shown).

[0073] Example 2

[0074] 872.48 mg of pyromellitic anhydride was added to 100 mL of 0.2 mol / L potassium hydroxide solution; the mixture was sealed with plastic wrap and stirred for 6 h to allow it to be fully hydrolyzed. Then, 180 mg of fructose was magnetically stirred in the above solution for 1 h to allow it to be dispersed and dissolved (n 羧基 :n 羟基 =8:5). Subsequently, the obtained mixed solution was titrated to pH=6 with 0.2 mol / L HNO3 solution and magnetically stirred for 2 hours. The obtained product was filtered and washed with deionized water and ethanol for 3 times. Then, it was dried in a 60°C forced air oven for 12 hours. After drying, a soft and hard carbon composite material precursor was obtained.

[0075] Example 3

[0076] Add 196.11 mg of cyclobutanetetracarboxylic dianhydride to 100 mL of 0.1 mol / L sodium hydroxide solution; seal with plastic wrap and stir for 4 h to fully hydrolyze. Then, add 270 mg of sucrose to the above solution and stir magnetically for 1 h to disperse and dissolve (n 羧基 :n 羟基=1:2). Subsequently, the obtained mixed solution was titrated to pH=6 with 1 mol / L HCl solution and magnetically stirred for 2 hours. The obtained product was filtered and washed with deionized water and ethanol for 3 times. Then, it was dried in a 60°C forced air oven for 12 hours. After drying, a soft and hard carbon composite material precursor was obtained.

[0077] Example 4

[0078] Add 4413 mg of biphenyltetracarboxylic anhydride to 100 mL of 0.1 mol / L sodium hydroxide solution; seal with plastic wrap and stir for 8 hours to fully hydrolyze. Then, add 180 mg of sucrose and 180 mg of glucose to the above solution and stir magnetically for 2 hours to disperse and dissolve (n 羧基 :n 羟基 =3:1). Subsequently, the obtained mixed solution was titrated to neutrality with 0.6 mol / L HCl solution and magnetically stirred for 2 hours. The obtained product was filtered and washed with deionized water and ethanol for 3 times. Then, it was dried in a 60°C forced air oven for 12 hours. After drying, a soft and hard carbon composite material precursor was obtained.

[0079] Example 5

[0080] 2681.76 mg of 1,4,5,8-naphthalenetetracarboxylic anhydride was added to 100 mL of 0.2 mol / L potassium hydroxide solution; the mixture was sealed with plastic wrap and stirred for 8 h to allow it to be fully hydrolyzed. Then, 855.75 mg of maltose was magnetically stirred in the above solution for 1 h to allow it to be dispersed and dissolved (n 羧基 :n 羟基 =1:1). Subsequently, the obtained mixed solution was titrated to pH=6.5 with 0.3 mol / L HN03 solution and magnetically stirred for 4 hours. The obtained product was filtered and washed with deionized water and ethanol for 3 times. Then, it was dried in a 60°C forced air oven for 12 hours. After drying, a soft and hard carbon composite material precursor was obtained.

[0081] Example 6

[0082] Add 1040.96 mg of bisphenol A diether dianhydride to 100 mL of 0.01 mol / L calcium hydroxide solution; seal with plastic wrap and stir for 2 h to fully hydrolyze. Then, add 171.15 mg of maltose to the above solution and stir magnetically for 2 h to disperse and dissolve (n 羧基 :n 羟基 =4:1). Subsequently, the obtained mixed solution was titrated to pH=5.5 with 0.01 mol / L HNO3 solution and magnetically stirred for 6 hours. The obtained product was filtered and washed with deionized water and ethanol for 3 times. Then, it was dried in a 60°C forced air oven for 12 hours. After drying, a soft and hard carbon composite material precursor was obtained.

[0083] Example 7

[0084] 426.4 mg of pyromellitic anhydride was added to 100 mL of 1 mol / L sodium hydroxide solution; the mixture was sealed with plastic wrap and stirred for 12 h to allow it to be fully hydrolyzed. Then, 1026.9 mg of maltose was magnetically stirred in the above solution for 2 h to allow it to be dispersed and dissolved (n 羧基 :n 羟基 =1:6). Subsequently, the obtained mixed solution was titrated to pH=4 with 2 mol / L H2SO4 solution and magnetically stirred for 1 hour. The obtained product was filtered and washed with deionized water and ethanol for 3 times. Then, it was dried in a 60°C forced air oven for 12 hours. After drying, a soft and hard carbon composite material precursor was obtained.

[0085] Example 8

[0086] The soft and hard carbon composite material precursor obtained in Example 1 was dried and loaded into a graphite boat, transferred to a tubular furnace, and heated to 500°C at 1°C / min under argon protection for 5 hours, then heated to 850°C at 1°C / min for 5 hours, then heated to 1100°C at 3°C / min for 6 hours for carbonization. After naturally cooling to room temperature, a black powder product was obtained.

[0087] Example 9

[0088] The soft and hard carbon composite material precursor obtained in Example 1 was dried and loaded into a graphite boat, transferred to a tubular furnace, and heated to 700°C at 5°C / min under argon protection and maintained for 1 hour, then heated to 900°C at 5°C / min and maintained for 1 hour, then heated to 1300°C at 10°C / min and maintained for 2 hours for carbonization. After naturally cooling to room temperature, a black powder product was obtained.

[0089] Comparative Example 1

[0090] This comparative example adopts the method in patent CN1 15849332A to conduct experiments and verify the difference in electrochemical properties of the obtained products.

[0091] Glucose and perylene tetracarboxylic acid dianhydride were added to ultrapure water at a ratio of 4:1 (mass ratio), wherein the mass of perylene tetracarboxylic acid dianhydride was 250 mg, and the obtained mixed liquid was magnetically stirred at 80°C, with a speed of 500 r / min. After 4 hours, the mixed liquid was rotary evaporated to remove the solvent to obtain a hard carbon precursor. The dried precursor was loaded into a graphite boat, transferred to a tube furnace, and heated to 600°C at 3°C / min for 2 hours under argon protection, then to 800°C at 4°C / min for 2 hours, and then to 1200°C at 5°C / min for 3 hours for carbonization, and a black powder product was obtained after natural cooling to room temperature.

[0092] The obtained product was used as the negative electrode material of potassium ion battery. After 500 cycles at a current density of 1000mA / g, its reversible specific capacity was only 55.3mAh / g.

[0093] Comparative Example 2

[0094] The difference between this comparative example and Example 1 is that no sodium hydroxide solution is added for hydrolysis.

[0095] Since the obtained precursor failed to undergo chemical bonding, glucose could not be separated from the solution by filtration, so only the soft carbon precursor participated in the heat treatment to form the final carbon material. The reversible specific capacity of the material was less than 10 mAh / g after 235 cycles at a current density of 1000 mA / g.

[0096] Comparative Example 3

[0097] The difference between this comparative example and Example 1 is that no HCl solution is added to titrate to pH <7.

[0098] In this comparative example, since hydrochloric acid was not added, the dianhydride substance after hydrolysis could not polymerize with glucose, and both of them were easily soluble in water, so the precursor material could not be obtained by suction filtration.

[0099] Comparative Example 4

[0100] Add 19.6 g of 3,4,9,10-perylenetetracarboxylic dianhydride to 100 mL of 0.1 mol / L sodium hydroxide solution; seal with plastic wrap and stir for 6 h to fully hydrolyze. Then, add 360 mg of glucose to the above solution and stir magnetically for 1 h to disperse and dissolve (n 羧基 :n 羟基 =5:1). Subsequently, the obtained mixed solution was titrated to neutrality with 1 mol / L HCl solution and magnetically stirred for 2 hours. The obtained product was filtered and washed with deionized water and ethanol for 3 times. Then, it was dried in a 60°C forced air oven for 12 hours to obtain an orange-red soft and hard carbon composite material precursor prepared by liquid phase intermolecular self-assembly.

[0101] In the prepared precursor, due to the high concentration of 3,4,9,10-perylenetetracarboxylic dianhydride, part of 3,4,9,10-perylenetetracarboxylic dianhydride did not participate in the chemical bonding reaction, resulting in local enrichment of the soft carbon precursor. Therefore, the composite material prepared by this material has a reversible specific capacity of 35.6 mAh / g after 500 cycles at a current density of 1000 mA / g.

[0102] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification with reference to the aforementioned embodiments, and obtained relatively ideal results. It should be understood that the above are only some embodiments of the present invention. It should be pointed out that for ordinary technicians in this field, other variations and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a soft and hard carbon composite material precursor, characterized in that: include: The soluble dianhydride substance is fully hydrolyzed in a strong alkaline solution to obtain a hydrolyzed solution; The hydrolysis solution is mixed with a soluble organic matter rich in hydroxyl groups, and the pH value of the obtained mixed solution is adjusted to induce targeted self-assembly at the molecular level to obtain a soft and hard carbon composite material precursor.

2. The preparation method according to claim 1, characterized in that: The soluble dianhydride substance has two acetyl groups, and the soluble dianhydride substance includes any one or a combination of two or more of 3,4,9,10-perylenetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, cyclobutanetetracarboxylic dianhydride, bisphenol A type diether dianhydride, pyromellitic dianhydride, and 1,4,5,8-naphthalenetetracarboxylic anhydride; And / or, the concentration of the soluble dianhydride substance in the strong alkaline solution is 0.005-0.5 mol / L.

3. The preparation method according to claim 1, characterized in that: The strong alkaline solution includes any one of sodium hydroxide solution, potassium hydroxide solution, and calcium hydroxide solution, or a combination of two or more thereof; and / or, the concentration of the strong alkaline solution is 0.01 to 1 mol / L; And / or, the preparation method comprises: adding a soluble dianhydride substance to a strong alkaline solution, stirring until fully hydrolyzed, to obtain a hydrolyzed solution; The stirring time is 2 to 12 hours.

4. The preparation method according to claim 1, characterized in that: The soluble organic matter having abundant hydroxyl groups includes any one of glucose, fructose, sucrose and maltose or a combination of two or more thereof; and / or, the ratio of the number of carboxyl groups of the soluble dianhydride substance after hydrolysis to the number of hydroxyl groups in the basic structural unit of the soluble organic matter rich in hydroxyl groups is 4:1 to 1:6; And / or, the preparation method comprises: adding a soluble organic substance rich in hydroxyl groups to the hydrolysis solution, and after uniform dissolution, titrating the resulting mixed solution with an acid solution to a pH value of 4 to 7, and continuing stirring for 1 to 6 hours; And / or, the acid solution includes any one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid; And / or, the concentration of the acid solution is 0.01-2 mol / L.

5. A soft and hard carbon composite material precursor prepared by the preparation method according to any one of claims 1 to 4, wherein the soft and hard carbon composite material precursor is highly uniform and has a tight interface.

6. A method for preparing a soft and hard carbon composite material, characterized in that: include: In a protective atmosphere, the soft and hard carbon composite material precursor obtained by the preparation method according to any one of claims 1 to 4 is carbonized to obtain a soft and hard carbon composite material.

7. The preparation method according to claim 6, characterized in that: The protective atmosphere comprises an argon atmosphere; And / or, the carbonization treatment includes: first heating to 500-700°C at a rate of 1-5°C / min for 1-5h, then heating to 800-900°C at a rate of 1-5°C / min for 1-5h, and finally heating to 1100-1300°C at a rate of 3-10°C / min for 2-6h to complete the carbonization treatment.

8. A soft and hard carbon composite material obtained by the preparation method according to claim 6 or 7.

9. Application of the soft and hard carbon composite material according to claim 8 in the field of battery energy storage, preferably, the application includes: Application of the soft and hard carbon composite material in the negative electrode of potassium ion battery.

10. A negative electrode material for a potassium ion battery, characterized in that: The invention comprises the soft and hard carbon composite material as described in claim 8.

Citation Information

Patent Citations

  • High-rate hard carbon negative electrode material and preparation method and application thereof

    CN115849332A